Inklusi dan Pemberdayaan Sosial: Mengembangkan Potensi Lokal di Desa Bahu Palawa, Kabupaten Pulang Pisau, Provinsi Kalimantan Tengah - Anam, M. Syaeful; Batubara, Muhammad Zusanri; Atem; Rahmatu, Habibah Pidi (Research and Development Agency Ministry of Home Affairs, 2024)
Government policy on village funds seeks to encourage village independence. Village independence can focus on development based on local potential. Studies on local potential-based village development have not yet explored the issues of social inclusion and community empowerment. This research analyzes the approach to social inclusion and community empowerment in developing local potential in Bahu Palawa Village. Social inclusion and community empowerment are important to study because these two aspects play a role in fostering more equitable, participatory, and sustainable development. This study uses Bennett's theoretical framework (2003) regarding social inclusion and community empowerment. This study uses a qualitative approach using three data collection techniques: observation, in-depth interviews, and document and literature study. Research findings show that the Bahu Palawa Village Government has tried to foster social inclusion and community empowerment in developing local potential. Social inclusion and community empowerment have not been running optimally due to a lack of access to basic services, awareness and knowledge, limited infrastructure, economic inequality, and the ineffectiveness of community empowerment programs. This condition inhibits citizen participation and prevents them from being fully involved in village development. In conclusion, developing local potential requires holistic social inclusion and empowerment development. This can be done through collaboration with a focus on increasing local capacity.